Economic Scheduling of Microgrid Based on Energy Management and Demand Response - Chamandoust Heydar (Electrical, Control and Communication Engineering, 2018)
Currently, microgrids are regarded one of the main substations in distribution networks that generate electrical energy locally. The advantages of microgrids include easy management, optimization, and highly reliable supply. In this paper, the recommended model is based on economic and emission optimal scheduling in connection to the main grid mode; implementation model implies the short-term mode with optimal operation units and the use of real-time pricing (RTP) plan. In this study, a multi-objective function for operating costs and emission with the augmented ɛ-constraint method has been considered; fuzzy decision-making process has been employed to obtain the best solution. In addition, it has been considered that a microgrid has interruptible and shiftable loads that can participate in demand response programs. The presented results have been evaluated based on different demand response programs.